Transformative Trajectories: An In-depth Analysis of ICT Integration in the Somali Higher Education System - Hashi, Abdinasir Ismael (International Journal of Computing and Engineering, 2025)
Purpose: This study aims to explore the transformative potential of Information and Communication Technology (ICT) integration within Somalia’s higher education sector. The research investigates how ICT can enhance academic achievement, increase accessibility, and improve the overall quality and relevance of higher education in the Somali context. Methodology: A mixed-methods approach was employed, combining quantitative and qualitative data collection techniques. Questionnaires were distributed to students and faculty, interviews were conducted with key stakeholders, and documentary analysis was performed to assess current policies, infrastructure, and ICT-related initiatives in higher education institutions. Findings: The research reveals a nuanced landscape of ICT integration in Somali higher education. While some institutions have begun adopting ICT tools, many face challenges including inadequate infrastructure, limited faculty training, and inconsistent policy support. Despite these barriers, significant potential exists for ICT to improve educational quality, promote student empowerment, and foster socioeconomic development. The study identifies positive correlations between ICT use and student performance, as well as institutional adaptability and innovation. Unique Contribution to Theory, Policy and Practice: The study offers a comprehensive analysis that bridges theoretical understanding and practical application of ICT in a fragile, post-conflict educational context. For theory, it contributes to the discourse on ICT in developing nations by contextualizing its adoption within Somalia’s unique socio-political landscape. For policy, it provides actionable recommendations aimed at strengthening infrastructure, faculty development, and regulatory frameworks. For practice, it guides institutions in designing sustainable ICT strategies that align with educational goals and national development priorities. The findings serve as a roadmap for educators, policymakers, and stakeholders aiming to harness ICT for transformative change in Somali higher education.